Organisational change : The assimilation of software technology in the higher education environment - Patel, Bhavna Atulkumar (My University, 2008)
Organizational change- its mechanisms, and its outcomes - is a topic of increasing interest and study in both business and education. The external environment, including the economic, political, and cultural dimensions of society is rapidly changing, growing in complexity and posing numerous challenges. The creation of the learning organisation is one of the responses to these challenges. During the 1990s the concept of the “learning organisation” attracted much attention and generated a significant amount of research. The central tenent of a learning organisation is that it is able to learn and therefore able to adapt better to both external and internal challenges. The study of how learning takes place in organisations has therefore become important in understanding organisational change. In the current research study, the implementation of an Enterprise Resource Planning (ERP) system meant that organisational change would be inevitable. New information technology software would result in changes in business processes, changes in work groups, changes in terminology and changes in how work is processed. The implication was that there would be a need for learning to take place in order for organisational change to take place. The Guttman’s Stage of Assimilation Model formed the theoretical basis for the research. A key assumption is that the assimilation of technology is best characterised as a process of organisational learning. The research findings indicated that learning did take place and Guttman’s model provided interesting insights into the different types of assimilation that took place at different level of the organisation. Interesting differences were found between academic and support staff and useful lessons were learned about how ERP systems can be introduced into higher education organisations. The current research findings also provided evidence that training and communication were crucial during a change process. These two elements are also vital in enabling organisational learning to take place.
Keywords: organisational change; Higher education; software technology